RESPONSE IMMUNITY OF GOLDFISH (Carassius auratus) INFECTED WITH Aeromonas hydrophila BACTERIA AND POST-TREATMENT WITH PROPOLIS SOLUTION - Riswan, M; Lukistyowati, Iesje; Syawal, Henni; Kurniawan, Ronal; Putri, Rianti; Putri, Mega Novia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study aims to determine the immunity response of Carassius auratus infected with Aeromonas hydrophila bacteria and post-treatment with propolis solution by measuring total leukocytes and phagocytosis index. The method used is experimental by applying a completely randomized design (CRD) with five treatments and three replications. The treatments were Kn (not infected with A. hydrophila and not treated with propolis), Kp (infected with A. hydrophila but not treated with propolis), while fish infected with A. hydrophila were treated with propolis doses P1 (700 ppm), P2 (800 ppm), and P3 (900 ppm). Treatment was done by injecting 0.1 ml of propolis into fish infected with A. hydrophila intramuscularly. The test material was 150 fish of 8-10 cm in size. The results showed that propolis significantly gave an immune response to the C. auratus infected with A. hydrophila (p<0.05). The 800 ppm propolis dose was the most effective, as indicated by a total leukocyte count of 3.70×104 cells/mm3, a phagocytosis index value of 28.33%, and a survival rate of 83.33%. This study highlights that propolis has potential as a natural immunostimulatory agent in enhancing non-specific defense mechanisms in C. auratus infected with pathogenic bacteria